Is There a Problem With Cognitive Outsourcing?. Issue 1 (October 2016) - Ahlstrom‐Vij, Kristoffer
Abstract: To what extent can we rely on others for information without such reliance becoming epistemically problematic? In this paper, this question is addressed in terms of a specific form of reliance: cognitive outsourcing . Cognitive outsourcing involves handing over ( outsourcing ) one's information collection and processing ( the cognitive ) to others. The specific question that will be asked about such outsourcing is if there is an epistemic problem about cognitive outsourcing as such . To ask if there is an epistemic problem with x for S is to ask if x is a problem for S 's ability to acquire true belief and avoid false belief. To ask if there is a problem for S with x as such is to ask if it is impossible to solve the problem for S while leaving x as is. I argue that, if we consider the five most plausible candidate epistemic problems raised by cognitive outsourcing—i.e., unreliability, gullibility, irrationality, dependency, and lack of epistemic autonomy—we see for each candidate that it is either not an epistemic problem, or not a problem about cognitive outsourcing as such.